Standard Setting Ujian Nasional Dengan Menggunakan Metode Angoff danBookmark - Arniati Prasedyawati Herkusumo (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this research is to find out the cut score of graduation for the national exam participants, as we know so far the determined passing score through judgement and the policy of the Government without paying attention to the matter of matter that exists on the test devices, and without involving the experts (as curriculum subjects teachers, expert, assessment expert). Determining graduation like this does not meet the criteria as signaled by experts such as educational measurement experts called in Standards for Educational and Psychological Testing : â€œWhen cut scores defining pass-fail, the judgmental process should be designed so that judges on bring their knowledge and experience to bear in a reasonable wayâ€. Scientific method that can be used to determine the score a passing grade is the Angoff method and bookmark method. This method can be used to determine the standard graduation test national became more scientific.